Estimation of the surface temperature in Landsat 5 historical images by means of single-channel atmospheric correction in the thermal for the Tempisque-Bebedero river basin (Costa Rica) - Martínez-Barbáchano, Rubén (2020)
In recent decades, the use of satellite imagery has increased to the point of being a fundamental tool in the monitoring of environmental processes and global change. In this sense, the historical importance of the Landsat family of satellites marks a milestone in 1985 with the introduction of the Tematic Mapper sensor, which offered users the possibility of acquiring information from an over 25-year historical database of thermal imagery at 120 meters of spatial resolution. This paper is presented as a methodology for obtaining surface temperature data from a time series of Landsat-5 TM images acquired in 2001 on the North Pacific Region of Costa Rica. The different algorithms that can be used for the estimation of surface temperature from Landsat data via the single-channel method by way of the inverse Planck function are presented. Prior to the calculation of the brightness temperature of the images, aspects such as average atmospheric transmissivity, ascending and descending radiance or earth´s surface emissivity were taken into account.